Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/biomedicines9070781
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mechanisms Contributing to Endothelial Dysfunction

Abstract: Maintenance of endothelial cell integrity is an important component of human health and disease since the endothelium can perform various functions including regulation of vascular tone, control of hemostasis and thrombosis, cellular adhesion, smooth muscle cell proliferation, and vascular inflammation. Endothelial dysfunction is encompassed by complex pathophysiology that is based on endothelial nitric oxide synthase uncoupling and endothelial activation following stimulation from various inflammatory mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
208
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(216 citation statements)
references
References 213 publications
3
208
3
2
Order By: Relevance
“…In addition to targeting HMGB1, a key driver of inflammatory and immune responses in numerous disease settings [ 86 89 ], miR-126 can target multiple other disease-associated genes of relevance to this study, including angiogenesis-related vascular endothelial growth factor A, sprouty-related protein-1, phosphoinositidol-3 kinase regulatory subunit-2 1, and the adapter molecule crk [ 90 92 ]. Our discovery that acidosis exerts marked control over HMBG1 and Bcl2 expression as well as downstream inflammation responders and Akt, via miR-126 and HIF-1 α (summarized in Figure 6 ), in the context of chronic ischemia is novel and represents important additions to our understanding of vascular inflammation and cell survival during ischemic disease, including atherosclerosis and vasculatures of solid tumors, wherein hypoxia and acidosis are integral disease components.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to targeting HMGB1, a key driver of inflammatory and immune responses in numerous disease settings [ 86 89 ], miR-126 can target multiple other disease-associated genes of relevance to this study, including angiogenesis-related vascular endothelial growth factor A, sprouty-related protein-1, phosphoinositidol-3 kinase regulatory subunit-2 1, and the adapter molecule crk [ 90 92 ]. Our discovery that acidosis exerts marked control over HMBG1 and Bcl2 expression as well as downstream inflammation responders and Akt, via miR-126 and HIF-1 α (summarized in Figure 6 ), in the context of chronic ischemia is novel and represents important additions to our understanding of vascular inflammation and cell survival during ischemic disease, including atherosclerosis and vasculatures of solid tumors, wherein hypoxia and acidosis are integral disease components.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological role of selectins, particularly P-Selectin and E-selectin, in atherosclerotic cardiovascular disease is supported both by experimental and human studies [7]. In particular, epidemiological studies have reported significant and positive associations between the concentration of soluble selectins and adverse cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the available evidence suggests that soluble selectins play a critical role in the pathophysiology of atherosclerosis and endothelial dysfunction and as markers of cardiovascular risk [7], and that interventions targeting this family of cell adhesion molecules might exert atheroprotective effects [13].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of adhesion molecules in endothelial cells is crucial for the effective adhesion of leukocytes, such as blood monocytes, to the endothelium and subsequent infiltration to the site of infection [28,29]. Thus, Icam-1, Vcam-1, E-selectin, and P-selectin represent key factors in endothelial inflammation and monocyte recruitment [29,30]. We therefore studied the expression of adhesion molecules in endothelial cells upon LPS stimulation, observing a strong and persistent increase (~10-20 fold) for Icam-1, Vcam-1, and E-selectin.…”
Section: Discussionmentioning
confidence: 99%